Sagot :
Answer:
a.
1. F(1) = 2(1) - 5 = 2 - 5 = -3
2. F(0) = 2(0) - 5 = 0 - 5 = -5
3. F(-1) = 2(-1) - 5 = -2 - 5 = -7
4. F(-3) = 2(-3) - 5 = -6 - 5 = -11
5. F(-2) = 2(-2) - 5 = -4 - 5 = -9
b.
1. F(1) = (1)² - 4(1) + 2 = 1 - 4 + 2 = -1
2. F(0) = (0)² - 4(0) + 2 = 0 - 0 + 2 = 2
3. F(-1) = (-1)² - 4(-1) + 2 = 1 + 4 + 2 = 7
4. F(-3) = (-3)² - 4(-3) + 2 = 9 + 12 + 2 = 23
5. F(-2) = (-2)² - 4(-2) + 2 = 4 + 8 + 2 = 14
In solving such functions, you just have the replace the value of x by the given value of x. F(x) can also be expressed as F(y) or G(x).
Answer:
A. F(x) = 2x - 5
1. f(1)= 2(1) - 5
= 2 - 5
= -3
2. f(0) = 2(0) - 5
= 0 - 5
= -3
3. f(-1) = 2 (-1) - 5
= -2 - 5
= -7 if both signs are negative, then the sign will also be negative. (sa subtraction)
4. f(-3) = 2 (-3) - 5
= -6 - 5
= - 11.
5. f(-2) = 2 (-2) - 5
= -4 -5
= -9
B. F(x) = x² - 4x + 2
1. f(1) = (1)² - 4(1) + 2
= 1 - 4 + 2
= -3 + 1
= -1
2. f(0)= (0)² -4(1) + 2
= 0 - 0 + 2
= 2
picture na sa sunod, medj katamad magtype haha
Step-by-step explanation:
lemme explain it to you. Naaral ko na to eh
So, don sa first part
1. F(1) = 2(x) - 5
┗ so kung anong nakalagay dito, yun din ang ilalagay mo sa isa pang 'x' kaya ang magiging result ay { F(1) = 2(1) - 5 }
┗ so magiging ganito sya
F(1) = 2(1) - 5
┗ multiply this one.
F(1) = 2 - 5
┗ syempre alam mo na this.
f(1) = -3 ☜ so this will be the final answer.
gets ba?? ;)